2017
DOI: 10.1016/j.cbpb.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and gene expression of multiple peptidoglycan recognition proteins (PGRPs) in the deep-sea mussel Bathymodiolus azoricus , involvement in symbiosis?

Abstract: The relationship between the deep-sea mussel Bathymodiolus azoricus and its thiotrophic (SOX) and methanotrophic (MOX) symbionts has been ecologically and functionally well studied.Endosymbiosis is common in deep-sea hydrothermal vent fauna, yet little is known about the molecular mechanisms underlying the regulation of interactions between host and symbionts. In this study we focused on a group of pattern recognition receptors (PRR), called PGRPs that are able to recognize the peptidoglycan of bacterial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The up-regulation of most of the PRRs at transcripts level only, supports this second hypothesis: mussels may have lined up storage of immune transcripts to respond adequately to a putative pathogen invasion. In contrast, the global down-regulation of another immune receptor (PGRP 3), seems to ascertain its role as a symbiont recruiter [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The up-regulation of most of the PRRs at transcripts level only, supports this second hypothesis: mussels may have lined up storage of immune transcripts to respond adequately to a putative pathogen invasion. In contrast, the global down-regulation of another immune receptor (PGRP 3), seems to ascertain its role as a symbiont recruiter [36].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a metabolic interdependence between B. azoricus and its symbionts has been evidenced using a proteo-genomic approach comparing aposymbiotic and symbiotic tissues [34]. While none of these studies have been validated in situ, it is noteworthy that pioneering attempts to do so have shown the putative role of two families of immune proteins in symbionts’ recognition and regulation [35, 36]. Although significant in the understanding of symbiotic association in deep-sea environments, these studies were either performed ex situ or limited to specific processes or families of genes, restricting our understanding on the mechanisms established by the host to manage its symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…Six short form PGRPs with conserved amidase activity have been revealed from Crassostrea gigas genome [72]. The lack of a signal peptide in the I. fruhstorferi PGRP_SC2 (If_PGRP_SC2) was in agreement to the short PGRPs screened from the EST database of deep- sea mussel, Bathymodiolus azoricus (Ba-PGRP 2 and Ba-PGRP 4) [73]. Further, the predicted secondary structure analysis for If_PGRP_SC2 show consistency with the three-dimensional model of BaPGRP 2 [73] and Drosophila PGRP-LB residues [74].…”
Section: Discussionmentioning
confidence: 77%
“…As suggested, PRRs mediated immune recognition of symbionts could be the fi rst step in initializing symbiosis. To date, multiple PRRs including Toll-like receptors (TLRs), immunoglobulin superfamily members (IgSF), peptidoglycan recognition proteins (PGRPs), lectins, and complement molecule (C1q) have been reported in Bathymodioline mussels and suggested their irreplaceable role in symbiosis (Bettencourt et al, 2009;Martins et al, 2014;Détrée et al, 2017;Zheng et al, 2017). What's more, it was reported that G .…”
Section: Immune Recognition Of Symbiontsmentioning
confidence: 99%